Geiger-Mode Avalanche Photodiode Arrays Integrated to All-Digital CMOS Circuits - Aull, Brian (Sensors (Basel), 2016)
This article reviews MIT Lincoln Laboratory's work over the past 20 years to develop photon-sensitive image sensors based on arrays of silicon Geiger-mode avalanche photodiodes. Integration of these detectors to all-digital CMOS readout circuits enable exquisitely sensitive solid-state imagers for lidar, wavefront sensing, and passive imaging.